Assured Data Storage: A Divide and Secure Multipart Algorithm for Cloud Storage - Vaikar, Ameya; Pawar, Deepak; Laddha, Yogesh (International Journal of Computer Sciences and Engineering, 2014)
This paper details about the single cloud and multi clouds security systems using MultiPart Secret Sharing Algorithm using Shamirï¿½s Secret and RSA algorithm and addresses possible solutions and methodology. Main focus of in this paper is on use of multi clouds and data security and reduces security risks and affects the cloud computing users using Multipart Secret sharing algorithm. It is a form of secret sharing, where a secret is divided into parts, which is giving each participant its own unique part, where some of the parts are required in order to reconstruct the secret. This algorithm is used where any ï¿½kï¿½ the parts are sufficient to reconstruct the original secret message, helping in Enhanced Security measures.